2019
DOI: 10.1177/0961203319829821
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms near IL-21 gene associated with Th17 cytokines confer risk for systemic lupus erythematosus in Chinese Han population

Abstract: Objective Interleukin-21 (IL-21) contributes to expansion, differentiation, and modulation of various immunocompetent cells. Deregulated production of IL-21 plays a role of cardinal significance in the pathogenesis of systemic lupus erythematosus (SLE). We aimed to determine whether single nucleotide polymorphisms (SNP) near the IL-21 gene have significant association with SLE susceptibility and the T helper-related inflammatory cytokine profile of SLE patients. Methods We enrolled 460 SLE patients and 460 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These observations indicate that IL-21 may be involved in the progression of multiple autoimmune diseases (Liu et al, 2015). Several pieces of literature have investigated the possible association between IL-21 SNPs and various autoimmune disorders, including MS, SLE, and RA (Gharibi et al, 2015, Meng et al, 2019, Ali et al, 2022, Carreño-Saavedra et al, 2023, revealing that IL-21 is a potential locus for autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate that IL-21 may be involved in the progression of multiple autoimmune diseases (Liu et al, 2015). Several pieces of literature have investigated the possible association between IL-21 SNPs and various autoimmune disorders, including MS, SLE, and RA (Gharibi et al, 2015, Meng et al, 2019, Ali et al, 2022, Carreño-Saavedra et al, 2023, revealing that IL-21 is a potential locus for autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…2 In particular, many studies have shown that genetic loci are associated with SLE susceptibility. 3…”
Section: Introductionmentioning
confidence: 99%
“…Understanding such pleiotropic effects of IL-6 in in the pathogenesis of the disease may help determine the progression, severity and duration of the disease. IL-6 is currently considered an important target for clinical interventions 28,29 . Hence, better understanding of IL-6 role in the pathogenesis of NODAT can provide rational and therapeutic intervention 29 .…”
mentioning
confidence: 99%
“…IL-6 is currently considered an important target for clinical interventions 28,29 . Hence, better understanding of IL-6 role in the pathogenesis of NODAT can provide rational and therapeutic intervention 29 . The guanine (G)/cytosine (C) polymorphism in the IL-6 proximal promoter region, at position IL-6 G (− 174) C, regulates transcription of the IL-6 gene and subsequently in IL-6 levels of plasma and serum 19,30 ; the same polymorphism was found to be associated with fasting insulin levels,insulin sensitivity, and the integrated area under the curve of serum glucose concentrations 30,31 .…”
mentioning
confidence: 99%